Solvent-based de-emulsification dispersive liquid-liquid microextraction coupled with UPLC-MS/MS for the fast determination of ultratrace levels of nitrated and oxygenated polycyclic aromatic hydrocarbons in environmental samples - Guiñez, María Evangelina (2018)
In this study, a new solvent-based de-emulsification dispersive liquid-liquid microextraction strategy followed by liquid chromatography-atmospheric pressure chemical ionization-tandem mass spectrometry has been developed for the determination of the ultratrace levels of nitrated and oxygenated polycyclic aromatic hydrocarbons present in environmental samples. Various parameters affecting the extraction efficiency such as type and volume of the extraction, dispersive and de-emulsifier solvents, temperature, salt addition, extraction time and sample volume were evaluated. Under optimal conditions, calibration plots were linear in the ranges between 0.005 ng mL-1 and 100 ng mL-1, with correlation coefficients (r2) better than 0.995. In addition, satisfactory extraction recoveries ranging from 95.1% to 98.5% were obtained. The proposed method has been found to have excellent detection sensitivity with limits of detection (LODs, S/N = 3) of 8.9-89.0 ng L-1 and precisions of 1.4-8.7% (RSDs, n = 5). Enrichment factors of the four target compounds were from 191-folds to 200-folds. The proposed method may be advised as an economical, fast easy, sensitive, accurate approach, even better than conventional DLLME and similar techniques. The results indicated that this methodology was suitable for the analysis of ultratraces of nitrated and oxygenated PAHs in water samples.